2023
DOI: 10.3390/neurolint15040076
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Neutrophil Extracellular Traps for Stroke Prognosis: A Promising Path

Eirini Liaptsi,
Ermis Merkouris,
Efthymia Polatidou
et al.

Abstract: Stroke has become the first cause of functional disability and one of the leading causes of mortality worldwide. Therefore, it is of crucial importance to develop accurate biomarkers to assess stroke risk and prognosis. Emerging evidence suggests that neutrophil extracellular trap (NET) levels may serve as a valuable biomarker to predict stroke occurrence and functional outcome. NETs are known to create a procoagulant state by serving as a scaffold for tissue factor (TF) and platelets inducing thrombosis by ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 54 publications
(153 reference statements)
0
5
0
Order By: Relevance
“…Recent results suggest that alterations in neutrophil function precede stroke onset rather than just being the effect of disease development, which may be the major difference in the role of neutrophils in the pathology of MS and stroke [97,98]. Moreover, the role of neutrophils and NETs in clot formation and ischemia/reperfusion injury made them one of the main factors contributing to stroke development and its exacerbation [93,94,[182][183][184][185] (Figure 3). Therapy regarding neutrophil depletion or inhibition has not succeeded.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent results suggest that alterations in neutrophil function precede stroke onset rather than just being the effect of disease development, which may be the major difference in the role of neutrophils in the pathology of MS and stroke [97,98]. Moreover, the role of neutrophils and NETs in clot formation and ischemia/reperfusion injury made them one of the main factors contributing to stroke development and its exacerbation [93,94,[182][183][184][185] (Figure 3). Therapy regarding neutrophil depletion or inhibition has not succeeded.…”
Section: Discussionmentioning
confidence: 99%
“…The work by Wang et al suggested that tPa directly induces NET formation under ischemic conditions [181]. NETs present in the thrombi were shown to complicate their dissolution and removal, resulting in worse clinical outcomes after recanalization therapies [182][183][184][185]. Abbasi et al showed that older thrombi (>4 h post-stroke onset) showed elevated levels of citrullinated histone H3 (the marker of NETs) and were stiffer, which makes them harder to dissolve by r-tPa [165].…”
Section: The Role Of Neutrophils In Reperfusion Processmentioning
confidence: 99%
“…Lesion volume or lesion location, age, stroke severity, and comorbid factors may influence stroke outcomes [42][43][44][45][46][47][48], but even mild stroke severity is not enough to provide an accurate prediction of favorable outcomes [49]. Thus, novel prognostic biomarkers are crucial for the development of personalized recovery treatment strategies [50] and the amelioration of patients' and caregivers' quality of life [51].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, it was discovered that the subgroup of patients with diabetes and acute hyperglycaemia had substantially elevated levels of NETs compared to individuals without these conditions [ 58 ]. Additionally, the correlation between the cumulative count of serum neutrophils and the concentrations of plasma NET markers in individuals experiencing acute stroke is linked to the severity of the stroke, as indicated by the NHISS score and infarct size, and is associated with an unfavourable prognosis [ 59 ].…”
Section: The Role Of Nets In Stroke Pathologymentioning
confidence: 99%
“…This modification enables targeted drug delivery to ischaemic lesions and facilitates controlled release. By regulating microglia, protecting the BBB, and promoting neuronal survival, C-Lipo/CA effectively mitigates the effects of ischaemia [ 59 ].…”
Section: Nets: Treatment For Strokementioning
confidence: 99%